Application of adaptive control in a refrigeration system to improve performance - Bandarra Filho,Enio Pedone (2011)
This paper reports an experimental investigation using adaptive control in a refrigeration system. This system is composed basically of a semi-hermetic compressor, concentric tubes heat exchangers, the condenser and evaporator, and thermostatic expansion valve (TXV). The refrigerant used in the refrigeration system was the HCFC-22 and also an AC frequency inverter was used to control the speed of the compressor. The temperatures were measured by PT-100 sensors and the pressures using piezoresistive pressure transducers. Data acquisition was implemented using the Labview software. An electronic card with analogical signal output was also used. These analogical signals were converted into digital through a Programmable Logic Controller (PLC) and then sent to the computer through a PC serial port. Tests were performed with a variable speed compressor in the range from 30 to 70 Hz and the experimental results showed that the highest performance (COP) was attained by working in the range of 50 Hz, using adaptive fuzzy control.